Changes in Body Fat and Related Biochemical Parameters Associated With Atypical Antipsychotic Drug Treatment in Schizophrenia Patients With or Without Metabolic Syndrome - Kornetova, Elena G.; Kornetov, Alexander N.; Mednova, Irina A.; Dubrovskaya, Viktoria V.; Boiko, Anastasia S.; Bokhan, Nikolay A.; Loonen, Anton J. M.; Ivanova, Svetlana A. (Frontiers in Psychiatry, 2019)
Background: Metabolic syndrome (MetS) is a common problem in schizophrenia patients and associated with increased mortality due to cardiovascular disease. Second generation antipsychotics (SGAs) play an important role in facilitating MetS. Objective: The study aimed to assess weight changes and alterations of indicators of body fat composition and lipid-glucose metabolism induced by reinitiating atypical antipsychotics in patients with schizophrenia when with or without metabolic syndrome. Methods: After giving Informed Consent, newly admitted patients with a clinical diagnosis of schizophrenia (ICD-10: F20) and an age between 18 and 55 years were included. MetS was diagnosed according to International Diabetes Federation (IDF)-criteria. At entry and after 6 weeks of treatment anthropometry and biochemical analysis was carried out. Total and visceral fat were measured with the use of non-invasive bioimpedance analysis and subcutaneous fat with calculation of total adipose tissue with the use of caliperometry. Based on biochemical assessments low density (LDL) and very low-density lipoproteins (VLDL), atherogenic index and Homeostatic Model Assessment of Insulin Resistance (IR–HOMA) were calculated. Statistical analysis was conducted using Wilcoxon signed-rank test, Mann-Whitney U-test, Chi-squared test. Differences were considered statistically significant at p<0.05. Results: A total of 114 patients (59M/55F) with schizophrenia were examined; they were divided into two groups with (n=43; 37.7%) and without (n=71; 62.3%) MetS. After a 6-weeks SGA-treatment only the total fat fold, waist circumference, triglyceride level and atherogenic index underwent statistically significant changes in patients with MetS. In those without MetS statistically significant changes across all fat indicators were noted. Also, a significant increase in blood glucose and HOMA-IR parameters, triglyceride and VLDL levels and atherogenic index was observed in this group. Discussion: The study illustrates the benefits of estimating both anthropometric and biochemical parameters shortly after (re)installing treatment of schizophrenia in order to minimize the risk of MetS development.